Experimental investigation of dry turning of AISI 1040 steel with TiN coated insert. (27th November 2019) - Nair, Sreejith S; Ramkumar, T; Selva kumar, M; Netto, Fabian
Abstract: Quality and productivity plays a pivotal part in the current manufacturing scenario. The current investigations are expected to evaluate the superlative handle environment which may fulfill the prerequisites of both quality as well as productivity. This work is centered on numerical modeling along with optimization model based on Box Behnken design strategy to optimize the machining parameters such as spindle speed, feed, depth of cut and nose radius on the reaction characteristics specifically, surface roughness (Ra) and material removal rate (MRR) during the dry turning of AISI 1040 steel utilizing TiN coated Carbide inserts. The results uncover that the spindle speed and the depth of cut are the foremost impacting factors that realize maximization of material removal rate and the minimization of surface roughness in dry turning of AISI 1040 steel. The optimization results illustrate that the desired combination of machining parameters for least surface roughness(Ra) of 1.15 μ m and high MRR of 22 568.2 mm 3 min −1 is obtained at the cutting speed of 1200 rpm, feed of 0.21 mm rev −1, depth of cut of 1.5 mm and nose radius of 1.2 mm.